Therapeutic management and care provided for neonates at the borderline of viability: opinions of medical school students - Anna Bogusława Pilewska-Kozak; Beata Dobrowolska; Celina Łepecka-Klusek; Agnieszka Bałanda-Bałdyga; Agnieszka Konstancja Pawłowska-Muc; Grażyna Stadnicka; Klaudia Pałucka; Karolina Depa (Kazimierz Wielki University, 2017)
Technological advances in the 20th c. and development of neonatology have created a chance to survive for the infants born before term, underdeveloped and unable to survive outside the  mother's womb. The triumph of reason over nature has given newborns a chance of undisturbed development, however there are infants who have no hopes to function independently, whose life is overburdened  with pain and suffering. From the ethical point of view all activities undertaken by the medical staff require respect for the human being and individualized management. The issues like decision as to continue or withheld resuscitation, differentiation between persistant therapy and euthanasia, withdrawal from persistant life supporting therapy and treatment, the limits of decision making  are the main dilemmas of the medical staff and parents. The purpose of study was to present opinions of the medical school students on the care of neonates born at the borderline of viability. The study was carried out in the group of 360 students of medical schools, 211 (58.6%) from the Medical University of Lublin, and 149 (41.4%) students of theMedicalUniversityinWrocław. The respondents were diagnostically surveyed by means of a questionnaire developed by the authors and evaluated by competent judges. The study was approved by the Ethical Board, Medical University of Lublin, No KE - 0254/180/2013.             The results revealed that over half respondents stated that it is impassible to define the limit of neonate's viability, i.e. maturity to live outsider the mother's womb and that each baby should be approached individually. The majority of students believed that resuscitation of a newborn on the verge of viability is the right approach. Almost every fourth student thought that the question should consider parental opinion, and 1/3 believed that once started, the treatment should be continued in any situation.